Effect of Continuity of Care on Quality of Life in Older Adults With Chronic Diseases: A Meta-Analysis. (June 2017) - Chen, Hsiao-Mei; Tu, Yi-Hsuan; Chen, Ching-Min
As the population ages, continuity of care (CoC) has increasingly become a particular important issue. Articles published from 1994 to 2014 were identified from electronic databases. Studies with randomized controlled design and elderly adults with chronic illness were included if Short Form-36 (SF-36) was used as an outcome indicator to evaluate the effect of CoC. Seven studies were included for analysis with the sum of 1, 394 participants. The results showed that CoC intervention can significantly improve physical function, physical role function, general health, social function, and vitality of QoL for elderly people with chronic disease.